2009
DOI: 10.1002/anie.200904379
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Addition of Halogens on Open Metal Sites in a Microporous Spin‐Crossover Coordination Polymer

Abstract: The last decade has witnessed a great activity in the realm of porous coordination polymers (PCPs). Their extreme chemical versatility and porosity has allowed chemists to consider PCPs as a new class of functional materials that are able to mimic, and even improve, the functions of zeolites, for example, storage, separation, and heterogeneous catalysis. [1] Furthermore, implementation of PCPs with solid-state properties (optical, magnetic, charge transport, etc.) would enable the expression of host-guest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(102 citation statements)
references
References 30 publications
4
93
0
1
Order By: Relevance
“…In previous sections we have already shown some examples that illustrate these possibilities. 67,68,97 (Fig. 1b).…”
Section: Electroactive Molecules@mofsmentioning
confidence: 94%
“…In previous sections we have already shown some examples that illustrate these possibilities. 67,68,97 (Fig. 1b).…”
Section: Electroactive Molecules@mofsmentioning
confidence: 94%
“…In particular, three-dimensional (3-D) Hofmann-type compounds {Fe II (pz)[M II (CN) 4 ]} (M = Ni, Pd, Pt), which show cooperative spin transitions have been actively investigated [43][44][45][46][47][48]. These compounds have 3-D porous frameworks consisting of cyanide-bridged Fe II M II bimetallic layers and the pillar ligand pz, and exhibit new functions coupling magnetic and adsorption properties, e.g., magnetic chemoswitching and modulation of the spin-transition temperature by guest molecules [45][46][47][48]. The tetracyanometallate SBUs play an important role in showing strong host-guest interactions as open-metal sites (OMS), however, the metal centres of OMS are limited to Ni II , Pd II and Pt II ions at this stage.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been shown that MOFs based on these molecular complexes exhibit magnetic switching at room temperature on physisorption of specific molecules within the porous framework 16,17 . The high sensitivity of these materials is also evidenced by the modification of the transition temperature on oxidative addition reactions following gas sorption at metal sites that are far from the magnetic centres 18,19 . A different approach to tune the magnetic properties of porous solids consists of the modification of the magnetic ground state of the MOF, which can be achieved through gas sorption processes that subtly affect the geometry of either the bridge between metal centres 20 or the ligand substituents 21 .…”
mentioning
confidence: 99%